2017
DOI: 10.18869/nirp.bcn.8.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Research Paper: Effect of Play-based Therapy on Metacognitive and Behavioral Aspects of Executive Function: A Randomized, Controlled, Clinical Trial on the Students With Learning Disabilities

Abstract: Introduction:Although the effect of educational methods on executive function (EF) is well known, training this function by a playful method is debatable. The current study aimed at investigating if a play-based intervention is effective on metacognitive and behavioral skills of EF in students with specific learning disabilities.Methods:In the current randomized, clinical trial, 49 subjects within the age range of 7 to 11 years with specific learning disabilities were randomly assigned into the intervention (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Studies have shown that intervention programs prepared using educational games can be effective in areas where students with difficulties experience problems such as attention and interest and in improving different cognitive functions (Emami Kashfi et al, 2019;Esmaili et al, 2017;García-Redondo et al 2019;). However, the results of the research show that the education of a neurosciencebased computer education program can significantly increase the cognitive performance of students with specific learning disabilities by developing different working memory skills such as speed, memory, attention, flexibility and problem solving (Gray et al, 2012;Sittiprapaporn, 2020).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Studies have shown that intervention programs prepared using educational games can be effective in areas where students with difficulties experience problems such as attention and interest and in improving different cognitive functions (Emami Kashfi et al, 2019;Esmaili et al, 2017;García-Redondo et al 2019;). However, the results of the research show that the education of a neurosciencebased computer education program can significantly increase the cognitive performance of students with specific learning disabilities by developing different working memory skills such as speed, memory, attention, flexibility and problem solving (Gray et al, 2012;Sittiprapaporn, 2020).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…The study used the experimental design and applied on (49) students, divided into two groups, experimental and control. The experimental group received a game-based intervention and the results revealed the impact of such an intervention on developing metacognitive and behavioural skills (Esmaili, Shafaroodi, Mehraban, Zarei, & Akbari-Zardkhaneh, 2017).…”
Section: Previous Studiesmentioning
confidence: 99%